Расчет и оптимизация выходного LC-фильтра импульсного преобразователя переменного напряжения - Голубев, В.В. (Технічна електродинаміка, 2012)
The design procedure and is offered to optimization of the target LC-filter of the converter of a AC voltage with a pulse regulator, active loading and high-frequency pulse-width regulation, simple engineering formulas for calculation of optimum parameters of the filter are received.